An evaluation of ankle blood pressures measured by the Doppler ultrasound technique in asymptomatic young smokers and non-smokers - Walters, M. M.,1930- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1990.